2021
DOI: 10.3390/insects12070613
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Spalangia endius (Hymenoptera: Pteromalidae) to Parasitize Bactrocera dorsalis (Diptera: Tephritidae) after Switching Hosts

Abstract: We studied the parasitism capacity of Spalangia endius as a pupal parasite of Bactocera dorsalis after switching hosts. We used pupae of B. dorsalis and M. domestica as the hosts and studied parasitism by S. endius in the laboratory. The parasitism capacities were compared at different host densities and different parasitoid ages. The two functional responses of S. endius fitted a Holling Type II equation. More M. domestica were parasitized than B. dorsalis at all the densities. The ability of S. endius to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Furthermore, the best precipitation in the warmest season is 534.99 mm, and the predicted suitability curve decreased slowly when the precipitation was greater than 534.99 mm, speculating that S. sichuanensis may have a strong adaptation to precipitation. Li et al (2021) place the parasitic wasp on paper or in a container and flood them with water [33]. The wasp can quickly escape from the water or float on the water and climb out along the container wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the best precipitation in the warmest season is 534.99 mm, and the predicted suitability curve decreased slowly when the precipitation was greater than 534.99 mm, speculating that S. sichuanensis may have a strong adaptation to precipitation. Li et al (2021) place the parasitic wasp on paper or in a container and flood them with water [33]. The wasp can quickly escape from the water or float on the water and climb out along the container wall.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial distribution area of species is an important ecological and evolutionary feature of species [ 9 ], and an essential prerequisite for mastering and using species [ 10 ]. At present, the limitations of conventional field survey methods limit our grasp of species distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Spalangia cameroni has been studied extensively, with mass-rearing methods developed to produce parasitoids on medfly hosts [34][35][36][37][38][39], host preferences for medfly and house fly [40], and interactions with other biological control agents of medfly [41]. Development of Spalangia endius was studied in guava fruit fly (Bactrocera correcta) and oriental fruit fly (B. dorsalis) [17,42], and a massrearing system was developed using medfly hosts [43]. Although there are no known reports of Muscidifurax spp.…”
Section: Discussionmentioning
confidence: 99%
“…Biological control of tephritid flies has been examined with a variety of different species of larval or pupal parasitoids [12,13] and proposed for use as biological control agents [12,14]. Laboratory and field studies have indicated that tephritoid flies are susceptible to several pteromalid pupal parasitoids that also commonly attack "filth flies" such as house flies and stable flies [15][16][17]. These parasitoids, mostly in the genera Muscidifurax, Spalangia, and Nasonia, have a wide host range and similar life histories [18].…”
Section: Introductionmentioning
confidence: 99%
“…The cosmopolitan S. endius is also a polyphagous dipteran ectoparasitoid, but mainly associated with tephritid and synanthropic ies (Morgan et al 1975). The three pupal parasitoid species can be successfully lab-reared (Wang et al 2016;Krüger et al 2019;Zheng et al 2021), but both P. vindemiae and T. anastrephae have shown potential as D. suzukii biological control agents (Garcia et al 2020b).…”
Section: Introductionmentioning
confidence: 99%